Low-viscosity ionic liquid–doped solid polymer electrolytes: Electrical, dielectric, and ion transport studies. (October 2018) - Gupta, Sandhya; Singh, Pramod K; Bhattacharya, B
Polymer electrolyte films based on poly(ethylene oxide) doped with salt sodium nitrate and ionic liquid (IL; 1-ethyl 3-methylimidazolium thiocyanate) have been prepared and characterized by differential scanning calorimetry (DSC) and impedance spectroscopy. The relative percentage of crystallinity of polymer electrolytes has been calculated by using DSC thermograms and electrical properties by using impedance spectroscopy. The incorporation of IL in polymer matrix increases the conductivity of polymer electrolyte. The maximum value of ionic conductivity of polymer electrolyte is found to be 1.93 × 10 −4 S m −1 with 9 wt% IL.